Rapid and Visual Detection of Porcine Parvovirus Using an ERA-CRISPR/Cas12a System Combined With Lateral Flow Dipstick Assay - Wei, Jing; Li, Yanan; Cao, Yingli; Liu, Qi; Yang, Kankan; Song, Xiangjun; Shao, Ying; Qi, Kezong; Tu, Jian (Frontiers in Cellular and Infection Microbiology, 2022)
Porcine parvovirus (PPV) is one of the important causes of pig reproductive diseases. The most prevalent methods for PPV authentication are the polymerase chain reaction (PCR), enzyme-linked immunosorbent assay (ELISA), and Quantitative Real-time PCR. However, these procedures have downsides, such as the fact that they take a long time and require expensive equipment. As a result, a rapid, obvious, and economical clinical diagnostic strategy for PPV patients is necessary. The ERA-CRISPR/Cas12a system for PPV detection was developed in this study, and three pairs of crRNA primers were generated to recognize the VP2 gene. The approach involved isothermal detection at 37°C, and the method can be used for visual inspection. The detection limit of the ERA-CRISPR/Cas12a system was 3.75 × 102 copies/μL, and no cross reactions with other porcine viruses were found. In view of the preceding, a rapid, visible, and low-cost nucleic acid testing approach for PPV has been developed using the ERA-CRISPR/Cas12a system.